How Characteristics of a Rainfall Event and the Meteorological Conditions Determine the Development of Stemflow: A Case Study of a Birch Tree - Zabret, Katarina; Šraj, Mojca (Frontiers in Forests and Global Change, 2021)
The process of rainfall partitioning is usually addressed by three components: rainfall interception, throughfall and stemflow. The occurrence and proportion of stemflow depends on many complexly interconnected factors. To contribute to the interpretation of these interdependencies, the influence of rainfall event characteristics and phenoseasons on stemflow development was analyzed with a new approach. In this study we have focused on the development of stemflow during 156 rainfall events with complete time series records for a single birch tree (Betula pendula Roth.) at a study plot in the city of Ljubljana, Slovenia. For each one of the selected events, diagrams of rainfall and stemflow development during the event were prepared and grouped according to their visual similarities using hierarchical clustering. Additionally, significant meteorological characteristics were determined for each group of events. Four characteristic types of stemflow response were identified and connected to the corresponding event characteristics. Events showing negligible stemflow response to rainfall increase were characterized with rainfall amounts lower than 5 mm, high rainfall intensities, and occurrence in the leafed phenophase. A slow stemflow increase, independent of the increase of the rainfall volume in the open, was recognized for rainfall events delivering less than 20 mm of rainfall during a 5-hour duration on average. The majority of these events were observed in the leafed phenophase, corresponding to higher air temperature and vapor pressure deficit. The occurrence of stemflow events, whose development followed the increase of the rainfall amount, was not dependent on the phenophase. However, during these events the average air temperature and vapor pressure deficit were lower, the rainfall amount was larger and the rainfall duration longer in comparison to the events showing independent increase with rainfall. The fourth type of response of stemflow was defined by a strong stemflow response in connection to large rainfall amounts and the longest rainfall duration, as observed for events in the leafless period. The four characteristic types of stemflow response provide additional information on the possible proportion of the rainfall reaching the ground as stemflow.